2010
DOI: 10.1371/journal.pone.0011200
|View full text |Cite
|
Sign up to set email alerts
|

A Low Molecular Weight Heparin Inhibits Experimental Metastasis in Mice Independently of the Endothelial Glycocalyx

Abstract: BackgroundSome low molecular weight heparins (LMWHs) prolong survival of cancer patients and inhibit experimental metastasis. The underlying mechanisms are still not clear but it has been suggested that LMWHs (at least in part) limit metastasis by preventing cancer cell-induced destruction of the endothelial glycocalyx.Methodology/Principal FindingsTo prove or refute this hypothesis, we determined the net effects of the endothelial glycocalyx in cancer cell extravasation and we assessed the anti-metastatic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…5B, C), we examined whether genes involved in endothelial cell sprouting and guidance were affected by enzymatic degradation. HepIII is known to be anti-angiogenic (Van Sluis et al, 2010) and we found that degrading luminal HS caused a decrease in vegfa expression. This was not associated with any specific vascular defects in the HepIII treated embryos.…”
Section: Discussionmentioning
confidence: 62%
“…5B, C), we examined whether genes involved in endothelial cell sprouting and guidance were affected by enzymatic degradation. HepIII is known to be anti-angiogenic (Van Sluis et al, 2010) and we found that degrading luminal HS caused a decrease in vegfa expression. This was not associated with any specific vascular defects in the HepIII treated embryos.…”
Section: Discussionmentioning
confidence: 62%
“…Van Sluis et al . injected B16F10 melanoma cells into the tail vein of mice with a C57Bl/6 background and observed metastasis to the lung over a 14‐day period. When hyaluronidase was injected prior to the melanoma cells or when syndecan‐1 −/− mice from the same background were similarly treated with melanoma cells, metastasis to the lung was inhibited significantly.…”
Section: Association Between the Gcx And Diseasementioning
confidence: 99%
“…Therefore, it has pro-metastatic properties. Heparin may also compete with the proteoglycan chains of heparin sulfate, which regulate metastasis formation [30]. …”
Section: Mechanisms Of Anti-cancer Actionmentioning
confidence: 99%
“…Almost complete elimination of metastatic tumors was observed in the wild type, and a lower reduction in the knock-out mice [30]. …”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%